Understanding the effects of siblings on child mortality: evidence from India - Gerald Makepeace; Sarmistha Pal (Institute for the Study of Labor (IZA), 2006)
Given the intrinsically sequential nature of child birth, timing of a child's birth has consequences not only for itself, but also for its older and younger siblings. The paper argues that prior and posterior spacing between consecutive siblings are thus important measures of intensity of sibling competition for limited parental resources. While the available estimates of child mortality tend to ignore the endogeneity of sibling composition, we use a correlated recursive model of prior and posterior spacing and child mortality to correct it. There is evidence that uncorrected estimates underestimate the effects of prior and posterior spacing on child mortality.
urn:nbn:de:101:1-2009040671
Keywords: 330; Familienplanung; Kindersterblichkeit; Kinderbetreuung; Familienökonomik; West Bengal; Indien